Cryptococcal chest wall mass and rib osteomyelitis associated with the use of fingolimod: A case report and literature review - Carpenter, Kent; Etemady-Deylamy, Ali; Costello, Victoria; Khasawneh, Mohammad; Chamberland, Robin; Tian, Katherine; Donlin, Maureen; Moreira-Walsh, Brenda; Reisenbichler, Emily; Abate, Getahun (Frontiers in Medicine, 2022)
Being introduced in 2010, fingolimod was among the first oral therapies for relapsing multiple sclerosis (MS). Since that time, postmarketing surveillance has noted several case reports of various cryptococcal infections associated with fingolimod use. To date, approximately 15 such case reports have been published. We present the first and unique case of cryptococcal chest wall mass and rib osteomyelitis associated with fingolimod use. The patient presented with left-side chest pain and was found to have a lower left chest wall mass. Computerized tomography (CT) showed chest wall mass with the destruction of left 7th rib. Aspirate from the mass grew Cryptococcus neoformans. The isolate was serotype A. Fingolimod was stopped. The patient received liposomal amphotericin B for 2 weeks and started on fluconazole with a plan to continue for 6–12 months. The follow-up CT in 6 weeks showed a marked decrease in the size of the chest wall mass. In conclusion, our case highlights the atypical and aggressive form of cryptococcal infection possibly related to immunosuppression from fingolimod use.